Nursing 2000: Collaboration to promote careers in registered nursing - Wilson, Connie S.; Mitchell, Barbara S. (Nursing outlook, 1999)
The effectiveness of the collaborative Nursing 2000 model in promoting careers in registered nursing was evaluated by a questionnaire distributed to 1598 nursing students. Results showed that 5 programs and activities administered by Nursing 2000 have been most influential in promoting careers in nursing.